Statistical Analysis of Comet Disconnection Events Using STEREO HI and a Data-assimilative Solar Wind Model - Sarah Watson; Chris Scott; Mathew Owens; Luke Barnard; Matthew Lang (The Astrophysical Journal)
Comets tails can reveal information about the local solar wind conditions. They can exhibit various signatures of interactions with the solar wind including bending, developing kinks, and sometimes undergoing tail disconnections. In this study, we investigate comet tail disconnection events observed in the STEREO HI data during the period of 2007–2023. Using the Heliospheric Upwind eXtrapolation model with a time-dependency (HUXt) solar wind model alongside novel solar wind data assimilation (DA) techniques, each disconnection event was investigated to determine its cause. The resulting statistical analysis led to three main conclusions: (1) for every heliospheric current sheet (HCS) crossing predicted by HUXt that occurs when the comet is within the region of influence of DA, a tail disconnection follows; (2) for HCS crossings that occur outside the region where DA can be applied, 54.5% are followed by a tail disconnection; and (3) there is an approximately linear relationship between the speed of the solar wind at the HCS crossing and the time delay to the onset of a disconnection given by the equation V _rel (km s ^−1 ) = (2.23 ± 0.35)Δ t (hr) + (400 ± 10)(km s ^−1 ).